OCULAR BAROTRAUMA PADA PENYELAM DI MASYARAKAT PESISIR - Adinda Citra Renda Gading; I Gede Suparta (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2022)
Ocular barotrauma is a condition where there is damage to the ocular and periorbital soft tissues due to pressure differences with the surrounding environment. In divers, ocular barotrauma is triggered by wearing an incorrect eye mask or googles. As a result, there are complaints of red eyes, subconjunctival hemorrhage, ecchymosis and even orbital bleeding or orbital emphysema. During a dive, the pressure will increase on the outside of the goggles or diving mask but the pressure inside remains at atmospheric values ​​so that it can produce negative pressure compared to the surroundings. Most cases of mild barotrauma do not require special treatment. Treatment that can be done depends on the severity of the tissue damage caused. In minor injuries to the skin such as bruises, the swelling will heal within one to two weeks with supportive care. This article aims to increase insight related to the incidence of ocular barotrauma in divers in coastal communities.